Droplet Size Distributions of Liquid‐Liquid Dispersions in Centrifugal Pumps. Issue 1 (3rd December 2020) - Schmitt, Philipp; Sibirtsev, Stephan; Hlawitschka, Mark W.; Styn, Robert; Jupke, Andreas; Bart, Hans‐Jörg
Abstract: The generation of liquid‐liquid dispersions with defined droplet size distributions is an important aspect for process equipment design. In this work, two centrifugal pumps with different impeller diameters were used to generate dispersions at selected operating points for a paraffin oil‐water system. The droplet break‐up phenomena within the centrifugal pumps were analyzed using a transparent pump design in combination with high‐speed imaging. Droplet size distributions at centrifugal pump discharge nozzle were recorded with optical probe measurement technologies and evaluated by means of image processing using a neural network. The influence of impeller diameter, rotational speed, volumetric flow rate and dispersed phase fraction are discussed. Experimental data is correlated using fluid properties, operating data as well as centrifugal pump dimensions. The correlations developed from results of this work serve as a basis for the equipment design of centrifugal pumps. Abstract : Generation of liquid‐liquid dispersions with a specific drop size distribution is an essential subprocess for reaction engineering and mass transfer for extraction processes. The droplet break‐up is investigated for two different centrifugal pumps using the test system paraffin oil‐water, and the results are correlated considering geometric data, material properties and operating parameters.